Antibody to virus components in volunteers experimentally infected with human coronavirus 229E group viruses. - Macnaughton, M R (1981)
Antibody rises to various virus subcomponents were measured by enzyme-linked immunosorbent assay in the paired sera of volunteers experimentally infected with human coronavirus 229E group viruses. Most of the antibody made during infection was directed against the virus surface projections, with only small amounts of antibody made against membrane or ribonucleoprotein components.